Manajemen risiko kepatuhan perbankan syariah berbasis prinsip syari’ah - Mustaqfiroh, Novi Kholifatul (Maliki Interdisciplinary Journal, 2024)
Bank financial institutions that operate in accordance with sharia law are known as Islamic banks. The study was conducted to find out the efforts to manage the compliance risk of Islamic banks are good. The research method uses a literature study, namely the data collection process is carried out through literature studies sourced from books, the internet and journals related to the themes discussed. The results obtained are There are 10 types of risks faced by Islamic banking. One of them is compliance risk, Compliance risk refers to Islamic banking is the risk borne by Failure to comply with and enforce Sharia laws, regulations, rules and principles. Islamic banks need to perform 10 compliance principles. The way to manage compliance risk management is to identify compliance risk, manage compliance risk and supervision.